Pengembangan Media Pembelajaran Game Monopoly untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran Tematik di Kelas VI Sekolah Dasar - Defa Defa; Ida Bagus Putrayasa; I Nyoman Sudana; Defa Defa; Ida Bagus Putrayasa (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The utilization of efficient and effective learning media is one of the learning successes. This Monopoly Game educational resource was created with elementary school students' needs and characteristics in mind. Where students in elementary school are still considered children. They also still enjoy playing. The Monopoly game learning media is designed to look like children's games, but its content is educational or learning related to the subject matter that sixth-grade elementary school students are studying, specifically Theme 7 leadership, which has three sub-themes. The teacher uses a variety of methods to get feedback from the students on what they've learned, but they don't do anything about it after they finish the material being studied. That is, students only receive a test question or exam after completing the material to determine their learning outcomes. Student learning outcomes appear to be lower than the specified KKM after using learning media. However, using this media led to an increase in the obtained learning outcomes, all of which were valid or met the KKM. Abstrak: Pemanfaatan media pembelajaran yang efisien dan efektif merupakan salah satu keberhasilan pembelajaran. Permainan Monopoli ini dibuat dengan mempertimbangkan kebutuhan dan karakteristik siswa sekolah dasar.dimana siswa sekolah dasar masih dianggap anak-anak.Mereka juga masih senang bermain. Media pembelajaran permainan monopoli dirancang agar terlihat seperti permainan anak-anak, namun isinya bersifat edukatif atau pembelajaran yang berkaitan dengan materi pelajaran yang dipelajari siswa kelas VI SD yaitu Tema 7 kepemimpinan yang memiliki tiga subtema. berbagai metode untuk mendapatkan umpan balik dari siswa tentang apa yang telah mereka pelajari, tetapi mereka tidak melakukan apa-apa setelah mereka menyelesaikan materi yang dipelajari. Artinya, siswa hanya menerima pertanyaan tes atau ujian setelah menyelesaikan materi untuk menentukan hasil belajarnya. Hasil belajar siswa tampak lebih rendah dari KKM yang ditentukan setelah menggunakan media pembelajaran. Namun penggunaan media ini menyebabkan peningkatan hasil belajar yang diperoleh semuanya valid atau memenuhi KKM.